Classroom Implementation Practices of the Secondary Level English Curriculum: A Case of Nepal - Karki, Manita (Journal of NELTA, 2015)
Curriculum is a whole educational programme to fulfil the objectives of national educational system that provides the fundamental frame for the teachers to teach in schools. The school level English language curriculum in Nepal aims at developing a comprehensive communicative competence in learners. This paper attempts to explore the extent to which English language teachers teaching at secondary level in Nepal understand the English curriculum and implement it in their classroom teaching. The paper is based on my graduate research project at Kathmandu University which involved eight English-language teachers from the Kathmandu valley for interview and observation to collect required information. The paper accomplishes the thesis that EFL teachers make sense of knowledge of curriculum at theoretical level; however it has not been utilized, as it should be, in their classroom practices. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12083 Journal of NELTA, Vol 19 No. 1-2, December 2014: 88-98